The Role of Promotion Strategy and Product Price on Purchase Intention of Indihome - Femmy Effendy; Reza Yonatan Hanata; Leo Nardo Setia Budi; Dhiraj Kelly Sawlani; Merrysa Christina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Indihome's promotion strategy has several obstacles in marketing its products and services to continue to maintain and develop existing markets and consumers, so the company needs to conduct various evaluations of the elements of promotional activities which not only function as a means of communication between companies and consumers, but also as tools for influencing consumers in purchasing activities or using services according to their wants and needs. The purpose of this study was to analyze the effect of promotional strategy on purchase intention, analyze the effect of price on Indihome's purchase intention and analyze the joint effect of price and promotion strategy on purchase intention of Indihome in DKI Jakarta. This study uses quantitative methods, and can determine the effect of the independent variables on the dependent variable. Through this research, an analysis of the promotion strategy and price variables can be carried out on buying interest. The objects in this study are people who purchase Indihome products, especially in the DKI Jakarta area by distributing questionnaires for research purposes, namely online by filling out the Google Form that has been provided by researchers. This study aims to answer the problems presented in the introduction chapter. Based on the results of the analysis and discussion, it can be concluded that the Promotion Strategy Variable (X1) does not have a significant influence on Purchase Intention (Y). Price Variable (X2) has a significant influence on Purchase Intention (Y). Promotion Strategy Variables (X1), Price (X2) have a significant influence together.